Optimization of Eye Shadow Powder Formula Preparation of Buni Fruit Extract (Antidesma bunius L. Spreng) as Natural Dye - Lestari, Neli Aulia; Hajrin, Wahida; Pratiwi, Eskarani Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The use of synthetic dyes in cosmetics can cause side effects such as allergies. Therefore, the presence of natural dyes such as anthocyanins from berries is a safer alternative for the community. However, the stability of anthocyanins as natural dyes can be affected by pH. The purpose of this study was to determine the optimum concentration of citric acid and tartaric acid in eyeshadow powder preparations as pH stabilizers using the Simplex Lattice Design method. The research method used the sonication method. Then, the formulation results from running SLD were carried out and evaluated for particle size, adhesiveness, and pH. Data analysis used SLD to obtain the optimum formula. Then, the evaluation was carried out as before with additional evaluations of organoleptic tests, homogeneity and polish. Furthermore, the data were verified statistically with a one-sample t-test. The results obtained an extract yield of 22.9% and a positive anthocyanin content. Based on the SLD method, the optimum formula was obtained with a citric acid concentration of 1.49% and a tartaric acid concentration of 0.508%. Verification of the optimum formula showed no significant difference between the experimental response and the predicted response with a pH value of 5.75 ± 0.12; adhesive power of 11.66 ± 1.52%; and particle size of 126.32 ± 2.02 μm. The conclusion is that the optimum formula produces good physical characteristics and the verification results show agreement between the predicted response and the experimental results.